On Construction of a Super Hierarchy of the Wadati-Konno-Ichikawa Equation - Xuemei Li; Lutong Li (Advances in Mathematical Physics)
In this paper, a super Wadati-Konno-Ichikawa (WKI) hierarchy associated with a 3×3 matrix spectral problem is derived with the help of the zero-curvature equation. We obtain the super bi-Hamiltonian structures by using of the super trace identity. Infinitely, many conserved laws of the super WKI equation are constructed by using spectral parameter expansions.